2018
DOI: 10.1177/0361198118772960
|View full text |Cite
|
Sign up to set email alerts
|

Data-Based Real-Time Moisture Modeling in Unsaturated Expansive Subgrade in Texas

Abstract: Moisture variations significantly influence the strength and stiffness of expansive subgrade soils, shortening the service lives of pavements and increasing the associated maintenance costs. Accurate measurements of soil moisture can be obtained through soil sampling and testing, but the process can be extensive and costly. Empirical models can accurately predict the moisture variations in an expansive subgrade in a shorter period of time, with lower accompanying costs. The objective of the current study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…It is generally accepted that the water content, void ratio and type of clay minerals in the soil are the main factors affecting the volume change potential of the soil [3][4][5]. On average, expansive soils in the United States incur more financial losses to the nation's infrastructure than earthquakes, floods, hurricanes, and tornadoes combined [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the water content, void ratio and type of clay minerals in the soil are the main factors affecting the volume change potential of the soil [3][4][5]. On average, expansive soils in the United States incur more financial losses to the nation's infrastructure than earthquakes, floods, hurricanes, and tornadoes combined [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [26] proposes a model using the Winkler foundation theory to analyze the pavement by considering it as a beam resting on expansive soil. Application of the developed models will facilitate noninvasive estimations of the response of soil strength and stiffness properties to variations in moisture [23].…”
Section: Resultsmentioning
confidence: 99%
“…A report showed that 60% of China's expressways require major repairs or renovations after 10~12 years of service, and 17% require such repairs after 6~8 years, indicating a shorter-than-expected service life for expressways [1]. Studies have found that subgrade moisture is one of the main causes of this problem [2][3][4]. Typically, the subgrade is compacted at its optimal moisture content to achieve optimal performance.…”
Section: Introductionmentioning
confidence: 99%